Germacrone, A Novel and Safe Anticancer Agent from Genus Curcuma: A Review of its Mechanism - Lou, Guanhua; Huang, Yan; Wang, Yu; Chen, Shiyun; Liu, Chang; Li, Ying; Feng, Jianan (Anti-Cancer Agents in Medicinal Chemistry, 2023)
Germacrone, a kind of natural sesquiterpenoid compound, has been reported to exhibit many pharmacological properties, especially the anticancer effect. Many in vitro experiments have been performed on various cancer cell lines, trying to explore their anticancer mechanism. Aiming at investigating the anticancer effect of germacrone, this article reviews the extant information on existing literature about germacrone-related studies. The anticancer mechanisms and clinical usages of germacrone are summarized. Literature databases (such as PubMed and CNKI) are used to search the current studies and experimental research about the anticancer effect information of germacrone. Anticancer mechanism of germacrone includes cell cycle arrest inducing, programmed cell death (apoptosis, autophagy, pyroptosis and ferroptosis) inducing, and estrogen-related genes mediating. Structural modification and analogue design are worthy of further study in the future.
Keywords: ferroptosis